Longitudinal study of malignancy associated changes in progressive cervical dysplasia - Strojan Fležar, Margareta (Radiology and oncology (Ljubljana), 1998)
Eight of 29 patients with progressive CIN were followed for 2 to 10 years. Their consecutive Pap smears were destained and stained according to Feulgen thionin method. Cyto-Savant/TM high resolution image cytometer (Oncometrics Technol. Corp., Vancouver, Canaderage values of muclear texture features and their probability distributions for consecutive Pap smears from each patient were calculated. Three out of 5 discriminant MAC, highDNAamount, highDNAcomp and highDNAarea, were to increase as a function of time in 5 out of 8 patients. A preliminary analysis which was performed on non-standardized archival material demonstrated a monotonous increase of discrete texture features as a function of time in patients with progressive CIN.
Keywords: Cell nucleus; Cervix dysplasia; diagnostika; Dna; ginekologija; Image cytometry; maternični vrat; rak (medicina)